Combination therapy of insulin‐like growth factor I and BTP‐2 markedly improves lipopolysaccharide‐induced liver injury in mice. Issue 8 (15th July 2022) - Nehme, Antoine; Ghahramanpouri, Mahdis; Ahmed, Iqbal; Golsorkhi, Mohadese; Thomas, Natasha; Munoz, Kevin; Abdipour, Amir; Tang, Xiaolei; Wilson, Sean M.; Wasnik, Samiksha; Baylink, David J.
Abstract: Acute liver injury is a common disease without effective therapy in humans. We sought to evaluate a combination therapy of insulin‐like growth factor 1 (IGF‐I) and BTP‐2 in a mouse liver injury model induced by lipopolysaccharide (LPS). We chose this model because LPS is known to increase the expression of the transcription factors related to systemic inflammation (i.e., NFκB, CREB, AP1, IRF 3, and NFAT), which depends on calcium signaling. Notably, these transcription factors all have pleiotropic effects and account for the other observed changes in tissue damage parameters. Additionally, LPS is also known to increase the genes associated with a tissue injury (e.g., NGAL, SOD, caspase 3, and type 1 collagen) and systemic expression of pro‐inflammatory cytokines. Finally, LPS compromises vascular integrity. Accordingly, IGF‐I was selected because its serum levels were shown to decrease during systemic inflammation. BTP‐2 was chosen because it was known to decrease cytosolic calcium, which is increased by LPS. This current study showed that IGF‐I, BTP‐2, or a combination therapy significantly altered and normalized all of the aforementioned LPS‐induced gene changes. Additionally, our therapies reduced the vascular leakage caused by LPS, as evidenced by the Evans blue dye technique. Furthermore, histopathologic studies showed that IGF‐I decreased the proportion of hepatocytes with ballooning degeneration. Finally, IGF‐I also increased the expression of the hepatic growth factor (HGF) and the receptor for the epidermal growth factor (EGFR), markers of liver regeneration. Collectively, our data suggest that a combination of IGF‐I and BTP‐2 is a promising therapy for acute liver injury.